Spinal Cord Compression by Tophaceous Gout with Fluorodeoxyglucose–Positron-Emission Tomographic/MR Fusion Imaging - Popovich, T.; Carpenter, J.S.; Rai, A.T.; Carson, L.V.; Williams, H.J.; Marano, G.D. (American Journal of Neuroradiology, 2006)
Summary: A 36-year-old woman presented with lower extremity paralysis. Her past medical history included gout. Conventional radiography and MR imaging revealed bone erosion and soft tissue lesions of the thoracic spine. Fluorodeoxyglucose–positron-emission tomographic (FDG-PET) images revealed hypermetabolic lesions of the thoracic spine. A CT-guided biopsy was diagnostic for inflammatory tophaceous gout. This case describes the CT, MR, and FDG-PET imaging characteristics of acute inflammatory gout. FDG-PET imaging characteristics of this disorder have not been previously described.